Towards tackling stunting in children in Rwanda under two-years-old: a multi-faceted approach - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
Stunting increases the risk of illness and premature death in children. It is associated with abnormal physical growth, delayed mental development, poorer school performance and later reduced productivity in the work force.